Heat transfer and optimum thermal resistance of bulk insulation for naturally ventilated building in tropical climates / Freda Morris - Morris, Freda (2015)
A study was carried out to evaluate the benefits of thermal insulation for naturally ventilated building in a tropical climate of Malaysia. The study was divided into two phases, the field study and simulation study. The field study was conducted in two identical test buildings with dimensions of 4m x 4m x 3m located in Universiti Teknologi MARA Shah Alam. Both test buildings have identical design. The non-insulated was named as Test Building A (TBA) while the insulated was named as Test Building B (TBB) where the insulation was installed consecutively underneath the roof and above the ceiling. This study presents the findings on thermal impact on the non-insulated TBA and insulated TBB. These were appraised by the respective attic and indoor temperature. The comparison of benefit of thermal insulation shows insulation underneath roof was better because the thermal impact for attic and indoor both test buildings indicate an advantage during daytime but ceiling insulation imposed penalty at daytime attic space. The simulation study was run to validate the software as a realistic representation of the real system. Since the respective percentage difference between field study and simulation study 4.2% and 6.1 %, the both data can be compared and new design of modelling will be able to predict other simulation data. This simulation study presents the findings on heat transfer and optimum of insulation thermal resistance to minimize the heat gain through building. The installation of thermal insulation at roof and wall consecutively has reduced the convective and radiative heat transfer but ceiling insulation has decreased the conductive, convective, and radiative heat transfer. The predominant heat transfer proportion through the envelope was via radiation. The determining of optimum thermal resistance of thermal insulation for several models was carried out to minimize heat gain through building. It was concluded that the optimum thermal resistance for thermal insulation installed at roof, ceiling, and wall was model R2 with respective thermal insulation 2.94 m².KW־¹ , 2.86 m².KW־¹ and 2.86 m².KW־¹.